2000
DOI: 10.2118/67835-pa
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Working Environment and Drilling Economics Through Better Understanding of Oil-Based Drilling Fluid Chemistry

Abstract: Summary The relationships between oil-based drilling fluid composition and the associated vapors have been quantified. The study documents the long- and short-term changes in base oil selection and fluid compositions. The study is based on the generation and assessment of data collected from the vapor emissions of oil-based drilling fluids with varying compositions and at a range of temperatures. The purpose of the study was to enable a better understanding of the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previously reported oil mist and vapour concentrations are, in contrast, oen based on samples collected to assess compliance with limit values or to document effect of technical control measures. 5,7,11 Exposure to oil mist and oil vapour in this study was low when compared to occupational exposure limits (OEL) in Norway of 0.6 and 30 mg m À3 (12 h TWA), respectively, as well as the OEL of 5 mg m À3 for inhalable oil mist from rened mineral oil (8 h TWA) recommended by the Scientic Committee on OEL, European Commission of Employment, Social Affairs and Inclusion. [21][22][23] Studies addressing possible health effects due to inhalation of oil mist and oil vapour exposure during oil drilling are lacking.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previously reported oil mist and vapour concentrations are, in contrast, oen based on samples collected to assess compliance with limit values or to document effect of technical control measures. 5,7,11 Exposure to oil mist and oil vapour in this study was low when compared to occupational exposure limits (OEL) in Norway of 0.6 and 30 mg m À3 (12 h TWA), respectively, as well as the OEL of 5 mg m À3 for inhalable oil mist from rened mineral oil (8 h TWA) recommended by the Scientic Committee on OEL, European Commission of Employment, Social Affairs and Inclusion. [21][22][23] Studies addressing possible health effects due to inhalation of oil mist and oil vapour exposure during oil drilling are lacking.…”
Section: Discussionmentioning
confidence: 74%
“…2 Although oil companies have their own surveillance programs, scientic publications presenting data on occupational airborne exposure during oil drilling are sparse. [3][4][5][6] These publications have shown that the total hydrocarbon air concentrations based on personal samples collected from the North Sea oil elds, are ranging from 10-200 mg m À3 at the drill oor and from 20-450 mg m À3 in the shaker area in the late 1980s. Later studies indicated oil mist air concentrations below 1 mg m À3 in personal samples.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of SDKP was characterized by FT-IR, 1 H-NMR, elemental analysis, and GPC. The optimal SDKP was obtained under the optimum reaction conditions: initiator concentration (by weight of monomer) 5 0.20%, reaction temperature 5 65 8C, mole ratio of NVCL/AMPS/DVB 5 60.0:38.0:2.0, SDS concentration (by weight of monomer) 5 2.0%, and pH value 5 7.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, as the move was made into high-temperature, high-pressure (HTHP) wells, a main challenge with water-based drilling fluid was related to the thermal degradation of drilling fluid additives, which could lead to rheological instability, filtration-control degradation, etc. 1,2 However, as the move was made into high-temperature, high-pressure (HTHP) wells, a main challenge with water-based drilling fluid was related to the thermal degradation of drilling fluid additives, which could lead to rheological instability, filtration-control degradation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…At extreme temperatures, special formulations and systems must be used 12–14. Since the 1980s, environmental legislation has increased restrictions on the use of oil‐based fluids, which possess high thermal stability, and progressively new water based formulations presenting improved properties for specific applications at high temperature are required 15–18. To avoid such problems, effective additives (especially fluid loss additives) are used to stabilize water‐bentonite suspensions at high temperature 19–24…”
Section: Introductionmentioning
confidence: 99%